Value addition in mushroom - Srivastava, Anuradha; Attri, B L; Sharma, V P (Indian Horticulture, 2020)
Mushroom with its immense health and nutritional benefits can solve many problems of under-nutrition and malnutrition. Despite this fact, mushroom cultivation and its utilization is not catching up fast because of its highly perishable nature. Thus, there is an urgent need of developing technologies to process mushrooms immediately into value added products which will not only cater to the protein and micronutrient requirement but at the same time will also solve the problem of postharvest losses of mushrooms. This article discusses some of the technologies developed by ICAR-Directorate of Mushroom Research, Solan to process mushrooms into value–added products with extended shelf life.